Gender and nation : a comparative analysis of state policies on gender in Turkey and Italy during the interwar period (1923-1938) - Mari, Francesca (My University, 2019)
Bu tez, iki savaş arası döneminde (1923 - 1938), İtalya ve Türkiye'de toplumsal cinsiyet ve milliyetçilik arasındaki ilişkiyi analiz etmeyi amaçlamaktadır. Tez özellikle, Mussolini ve Atatürk’ün Kemalist ve Faşist rejimleri döneminde kabul edilen toplumsal cinsiyet politikalarına odaklanıyor. Tezde Karşılaştırmalı-Tarihsel Metodoloji (CHM) ve feminist teori kullanılarak, yükselen İtalyan ve Türk milliyetçiliği analiz edilip toplumsal cinsiyet sorunuyla ilişkilendirildi. Bu tez, devlet politikaları ve bu politikaların, kadınların yaşamları üzerindeki etkileri hakkında karşılaştırmalı bir yorum sunuyor. Bu tez, iki dünya savaşı arası dönemde İtalya’da psikiyatri hastanelerinde tutulan orijinal kaynakları, süreli yayınları, günlükleri ve hasta kayıtlarını inceleyerek, kadınların zor koşullarını yeniden inşa ediyor. Ayrıca bu tez, Atatürk ve Mussolini dönemi rejimleri arasındaki yapısal farklılığı ve bunun sonucundaki toplumsal cinsiyet politikası farklılığının altını çiziyor. Bu tez, Mussolini’nin rejimiyle ilgili olarak, faşist ideoloji ile milliyetçi ideoloji arasındaki farkı gösterir ve siyasi karar almada erkek egemenliğini vurgular. Bu tezde, iki savaş arası dönemde hem İtalya hem Türkiye’deki liderlerin toplumsal cinsiyet politikalarını etkileyen milliyetçi bir politika benimsediklerini savunuyorum. Atatürk’ün laik ve özgürleştirici-feminist tutumu, antifaşist kadınlara baskı yapan ve hapse atan Mussoloii’nin mizojinist anti-feminizminden açıkça farklıydı. Bu nedenle Atatürk için milliyetçilikten, Mussolini rejimi için de faşizmden söz edebiliriz.

This thesis aims to analyze the relationship between gender and nationalism, in Italy and Turkey, during the interwar period (1923 – 1938). Especially, it focuses on Mussolini and Atatürk’s gender policies adopted from the Kemalist and Fascist regimes. Trought the use of Comparative-Historical Methodology (CHM) and the feminist critical theory, I will analyze and compare the rising of Italian and Turkish nationalism, connecting this to the gender issue. This thesis provides a new interpretation about state policies and their effect on women's lives. By analyzing the original legislative codes, periodicals, diaries and the publications of patient records detained in psychiatric hospitals in Italy during the two World War, this thesis reconstructs the harsh condition of women during that historical period. In order to substantiate this argument, this study investigates the structure of patriarchy and its development in Turkish and Italian societies. Moreover, this thesis highlights the structural difference of the Atatürk’s regime from that of Mussolini and their different gender policies. Particularly, regarding the Mussolini’s regime, this thesis underlines male egemony in political decision making, demonstrating the difference between fascist ideology and nationalist ideology.In this thesis I argue that during the interwar period, both leaders in Italy and Turkey adopted a nationalist policy that effected the gender policies. The secular and emancipasionist-feminist attitude of the Atatürk’s clearly differed from the Mussolini’s anti-feminist misogyny who oppressed and persecuted anti-fascist women. For this reason, we can speak of nationalism in the case of Atatürk and fascism for Mussolini’s regime
Keywords: Atatürk; cinsiyet politikaları; Fascism and Kemalism; faşizm ve kemalizm; gender policies; International relations; iki savaşı arası dönem; kadın hakları ve kadın hareketleri Interwar period; milliyetçilik; Mussolini; Mussolini and Atatürk; nationalism; Political science; Siyasal bilim; Uluslararası ilişkiler; women’s rights and women’s movements